Upaya Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Membuat Poster Melalui Pendekatan Keterampilan Proses Berbasis Android - Fitri Gurnitasari (Jurnal Didaktika Pendidikan Dasar, 2020)
This study aims to describe efforts to improve student learning outcomes in learning to make posters through an Android-based process skill approach. With the Classroom Action Research (CAR) method it has been proven that the Android-based process skills approach to learning to make posters can improve the learning process, student activities, and student learning outcomes which are characterized by an increase in student learning processes from an average score of 2 (50%) categories enough in pre-action, it became 3 (75%) good categories in cycle 1 (increased by 25%), and increased in cycle 2 to 3.2 (80%) with very good categories (increased by 5%). Secondly, the increase in student learning activities from an average score of 3 (60%) is sufficient in the pre-action category, to 4 (80%) in the high category in cycle 1 (increased by 20%) and progressively increases in cycle 2 by increasing the average score to 4.4 (87%) the category is very high (an increase of 7%). Third, the increase in student learning outcomes on average 82 (25%) in pre-action to 85 (75%) in cycle 1 (increased 50%) and increased in cycle 2 to 88 (90%). Based on the analysis of practical applications it can be concluded that the approach of the Android-based process skills can improve student learning outcomes in learning to make posters.